Differences Between Takotsubo and the Working Diagnosis of Myocardial Infarction With Nonobstructive Coronary Arteries - Lopez-Pais, Javier; Izquierdo Coronel, Bárbara; Raposeiras-Roubín, Sergio; Álvarez Rodriguez, Leyre; Vedia, Oscar; Almendro-Delia, Manuel; Sionis, Alessandro; Martin-Garcia, Agustin C.; Uribarri, Aitor; Blanco, Emilia; Martín de Miguel, Irene; Abu-Assi, Emad; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Whether Takotsubo syndrome (TTS) should be classified within myocardial infarction with non-obstructive coronary arteries (MINOCA) is still controversial. The aim of this work was to evaluate the main differences between TTS and non-TTS MINOCA. Methods and Results: A cohort study based on two prospective registries: TTS from the XXXX1 registry (N:1055) and non-TTS MINOCA patients from contemporary records of acute myocardial infarction from 5 national centers (N:1080). Definitions and management recommended by the ESC were used. Survival analysis was based on Cox regression; propensity score matching (PS) was created to adjust prognostic variables. TTS were more often women (85.9% vs. 51.9%; p<0.001) and older (69.4±12.5 vs. 64.5±14.1 years; p<0.001). Atrial fibrillation was more frequent in non-TTS MINOCA (10.4% vs. 14.4%; p 0.007). Psychiatric disorders were more prevalent in TTS (15.5% vs. 10.2%, p<0.001). In-hospital mortality and complications were higher in TTS: 3.4 vs 1.8%, (p 0.015) and 25.8% vs. 11.5%, (p<0.001). Global mortality before PS matching was 16.1% in non-TTS MINOCA and 8.1% in TTS. Median follow-up was 32.4 months; after PS matching, TTS had less major adverse cardiovascular events (MACE): Hazard Ratio (HR) 0.59; 95% confidence interval (CI) 0.42 to 0.83. There were no differences in global mortality (HR 0.87; CI: 0.64 to 1.19), but TTS had lower cardiovascular mortality (HR 0.58; CI: 0.35 to 0.98). Conclusions: Compared to the rest of MINOCA, TTS presents a different patient profile and a more aggressive acute phase. However, its long-term cardiovascular prognosis is better. These results support that TTS should be considered a separate entity with unique characteristics and prognosis.